PERAN PENGAWAS DALAM PENERAPAN MANAJEMEN MUTU TERPADU DI SEKOLAH - Ahmad Hariyadi (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2014)
One of the policy conducted by the government in an effort to build up the quality of education is the application of total quality management in schools. Providing integrated quality management in schools requires the cooperation of principals, teachers and employees as utama. Executive management function does not just stop at the implementation stage, but there is still the stage control or supervision. In the formal education supervisory functions assigned to the office of school inspector. To describe the profile of the school superintendent, the concept of integrated quality management and how the supervisory role in the implementation of total quality management in schools. School superintendent is implementing functional techniques in the field of academic and managerial oversight on a number of educational units ditetapkan.Tanggung school superintendent is responsible to achieve the quality of education in schools is cultivated. While the integrated quality management is a way of managing educational institutions with continuous improvements made on services, people, products, and environment in order to meet the needs, desires and expectations of its customers, today and for the foreseeable future. In the implementation of total quality management supervisor role may be implied by the eight competencies supervisor of thought Wiles and Bondi, namely as a developer of students, curriculum, instructional specialists, human relations worker, staff developers, administrators developer, manager changes, and evaluators.